2020
DOI: 10.1186/s40694-020-00098-w
|View full text |Cite
|
Sign up to set email alerts
|

Functional production of human antibody by the filamentous fungus Aspergillus oryzae

Abstract: Background: Monoclonal antibodies (mAbs) as biopharmaceuticals take a pivotal role in the current therapeutic applications. Generally mammalian cell lines, such as those derived from Chinese hamster ovaries (CHO), are used to produce the recombinant antibody. However, there are still concerns about the high cost and the risk of pathogenic contamination when using mammalian cells. Aspergillus oryzae, a filamentous fungus recognized as a GRAS (Generally Regarded As Safe) organism, has an ability to secrete a lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…For instance, adalimumab, a human anti-TNFα antibody, was produced by fusing it with AmyB, a α-amylase. Then, CRISPR/Cas9-based genome editing was used to delete the Aooch1 encoding a key enzyme of hyper-mannosylation process, to assess the recombinant antibody’s capacity to bind to FcγRIIIa [ 90 ]. This genome editing system was used to investigate the functional characterization of glycerol dehydrogenase, revealing that AoGld3, a glycerol dehydrogenase, is involved in the production of the secondary metabolite kojic acid by influencing the expression of kojA (an enzyme gene) and kojR (a transcription factor gene) involved in the kojic acid biosynthesis [ 91 ].…”
Section: Development and Application Of Crispr/cas9-based Genome Edit...mentioning
confidence: 99%
“…For instance, adalimumab, a human anti-TNFα antibody, was produced by fusing it with AmyB, a α-amylase. Then, CRISPR/Cas9-based genome editing was used to delete the Aooch1 encoding a key enzyme of hyper-mannosylation process, to assess the recombinant antibody’s capacity to bind to FcγRIIIa [ 90 ]. This genome editing system was used to investigate the functional characterization of glycerol dehydrogenase, revealing that AoGld3, a glycerol dehydrogenase, is involved in the production of the secondary metabolite kojic acid by influencing the expression of kojA (an enzyme gene) and kojR (a transcription factor gene) involved in the kojic acid biosynthesis [ 91 ].…”
Section: Development and Application Of Crispr/cas9-based Genome Edit...mentioning
confidence: 99%
“…This study showed that the repeatable marker-free genome editing approach can effectively delete or integrate multiple genes in the industrial A. oryzae strain ( Katayama et al, 2019 ). In the production experiment of human antibody (anti-TNFα antibody adalimumab) by A. oryzae , the CRISPR/Cas9 technique was used for the deletion of the Aooch1 gene, which encodes a key enzyme for the hypermannosylation process, to detect the binding ability of the recombinant antibody with FcγRIIIa ( Huynh et al, 2020 ). In addition, the CRISPR/Cas9 system was also used to delete AoGld3 , which is one of 45 glycerol dehydrogenase genes in A. oryzae , to investigate its effect on the production of the secondary metabolite kojic acid.…”
Section: Development Of Transformation Systems Of a Oryzaementioning
confidence: 99%
“…Adalimumab has been used in the treatment of some chronic inflammatory diseases such as rheumatoid arthritis. Production of adalimumab was successfully conducted in the culture supernatant of A. oryzae transformants with comparable affinities and bioactivities to its commercial counterpart (Huynh et al 2020).…”
Section: Functional Production Of Human Pharmaceutical Proteins Using a Oryzaementioning
confidence: 99%